Combined Test for Assessment of Anterior Pituitary Function. Issue 5888 (10th November 1973) - Harsoulis, P.; Marshall, J. C.; Kuku, S. F.; Burke, C. W.; London, D. R.; Fraser, T. R.
Abstract : A combined test consisting of the simultaneous administration of insulin, thyrotrophin-releasing hormone (TRH), and luteinizing hormone and follicle stimulating hormone-releasing hormone (LH/FSH-RH) was performed in 24 people. Eleven of these also had the three individual tests performed separately, and the remaining 13 had a separate test of either LH/FSH-RH and TRH together or singly at a later date. In both normal people and patients, whether the tests were performed alone or in combination, no difference was found between the hormone responses (growth hormone, cortisol, LH, FSH, thyroid-stimulating hormone) seen to these stimuli. It is proposed that combined administration of insulin and the hypothalamic releasing hormones may be used as a single test for the assessment of anterior pituitary function. The test is convenient and time saving, and with care can be performed in outpatients.